2008
DOI: 10.4067/s0301-732x2008000200008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of artificially induced spinal cord compression on the canine cervical internal vertebral venous plexus: comparative evaluation of computed tomographic venography and digital subtraction venography

Abstract: Effects of artificially induced spinal cord compression on the canine cervical internal vertebral venous plexus: comparative evaluation of computed tomographic venography and digital subtraction venographyEfectos de la compresión de la médula espinal inducida artificialmente sobre el plexo venoso vertebral interno cervical en el perro: evaluación comparativa mediante venografía por tomografía computarizada y venografía por substracción digital RESUMENEl plexo venoso vertebral interno (PVVI) es una red vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Currently there are no reports in the veterinary literature that describe a specific underlying cause of a vertebral venous system abnormality. However, one study has looked at the effects of artificial spinal cord compression on the internal vertebral venous plexus . This study showed an increase in transverse diameter of the internal vertebral venous plexus immediately cranial and caudal to the site of compression.…”
Section: Discussionsupporting
confidence: 91%
“…Currently there are no reports in the veterinary literature that describe a specific underlying cause of a vertebral venous system abnormality. However, one study has looked at the effects of artificial spinal cord compression on the internal vertebral venous plexus . This study showed an increase in transverse diameter of the internal vertebral venous plexus immediately cranial and caudal to the site of compression.…”
Section: Discussionsupporting
confidence: 91%
“…In humans, posterior internal vertebral venous plexuses are described posterolat-erally to the spinal cord in the peridural space. 24,25 Posterior internal vertebral venous plexuses communicate with anterior internal vertebral venous plexuses through ladder-like transverse connecting veins that are equivalent to IABs in dogs. 25 Anecdotal references to dorsal internal vertebral plexuses have been reported in veterinary medicine, but such structures were not evident in our study.…”
Section: Discussionmentioning
confidence: 99%